"That was intense!" Spirituality during childbirth: a mixed-method comparative study of mothers' and fathers' experiences in a public hospital. Issue 1 (December 2016) - Bélanger-Lévesque, Marie-Noëlle; Dumas, Marc; Blouin, Simon; Pasquier, Jean-Charles
Abstract Background While spirituality is well described in end-of-life care literature, research on its place in the delivery room remains largely limited to mother-oriented qualitative studies focusing on life-threatening situations (e.g., high-risk pregnancies). Our aim was to compare mothers' and fathers' spirituality during childbirth. Methods A mixed methods questionnaire was developed from our childbirth-related spirituality categorization and distributed to all parents of newborns, 12–24 h postpartum, over 45 consecutive days. Paired-sample t-tests and qualitative thematic analysis were used to compare mothers and fathers. Multiple linear regressions identified factors associated with their respective global scores (vaginal and cesarean deliveries separately). Results The global scores for mothers (38.6/50) and fathers (37.2/50) were similarly high (N = 197;p = 0.001). Highest-ranked ("respect", "moral responsibility", "beauty of life", "gratitude") and lowest-ranked spiritual themes ("prayer", "greater than self") were in agreement. Fathers scored higher on "fragility of life" (p = 0.006) and mothers on "self-accomplishment" (p‹0.001), "letting go" (p‹0.001), and "meaningfulness" (p = 0.003). "Admission of baby in neonatal unit" was associated with higher global score for both mothers and fathers. Other factors also increased fathers' (witnessing a severe tear) and mothers' scores (birthplace outside Canada; for vaginal deliveries, religious belonging and longer pushing stage). Conclusion These first quantitative data on the prevalence of spirituality during childbirth highlight a high score for both parents, among a non-selected public hospital population. Spirituality emerges not only from unordinary situations but from any childbirth as an "intensification of the human experience". Significant differences for some spiritual themes indicate the need to consider the spirituality of both parents.